2012
DOI: 10.1161/cir.0b013e31825d59fd
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Psychological Interventions to Improve Outcomes for Recipients of Implantable Cardioverter Defibrillators and Their Families

Abstract: Abstract-Significant mortality benefits have been documented in recipients of implantable cardioverter defibrillators (ICDs); however, the psychosocial distress created by the underlying arrhythmia and its potential treatments in patients and family members may be underappreciated by clinical care teams. The disentanglement of cardiac disease and device-related concerns is difficult. The majority of ICD patients and families successfully adjust to the ICD, but optimal care pathways may require additional psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1
23

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 224 publications
(254 reference statements)
4
131
1
23
Order By: Relevance
“…Odpowiednia ocena i leczenie dystresu psychologicznego powinny więc być integralną częścią postępowania klinicznego. Wszyscy pacjenci z ICD, a w szczególności ci wykazujący dystres, wymagają wsparcia dotyczącego tego, jak żyć z wszczepionym urządze-niem w celu poprawy wyników leczenia [238].…”
Section: Psychospołeczne Następstwa Leczenia Za Pomocą Implantowanychunclassified
“…Odpowiednia ocena i leczenie dystresu psychologicznego powinny więc być integralną częścią postępowania klinicznego. Wszyscy pacjenci z ICD, a w szczególności ci wykazujący dystres, wymagają wsparcia dotyczącego tego, jak żyć z wszczepionym urządze-niem w celu poprawy wyników leczenia [238].…”
Section: Psychospołeczne Następstwa Leczenia Za Pomocą Implantowanychunclassified
“…43 Integration of informal caregiving costs into economic evaluations of illnesses such as CVD will help to avoid underinvesting for intervention strategies for these conditions. 43 For example, several studies have been designed and tested with informal caregivers of individuals with heart failure 13,[62][63][64][86][87][88][89] and stroke, [90][91][92] with some including cost analyses or estimated costs of intervention delivery. 93,94 Scientific guidelines recommend that informal caregivers be included in the care of individuals with CVD, 86,90,95 yet implementation of evidence-based strategies to support informal caregivers remains a challenge in today's healthcare system, primarily because of a lack of allocated resources within healthcare systems.…”
Section: Future Research Opportunities and Policy Implications Researmentioning
confidence: 99%
“…[75][76][77][78][79] Research has shown that 25% of ICD recipients experience depression or anxiety problems, 80 with the majority receiving no formal treatment for psychological problems. 81 Only 3 out of 44 patients in our study disclosed psychological problems attributable to device implantation, which is lower than previous research.…”
Section: Implications For the Development Of Decision-support Toolsmentioning
confidence: 99%